Investigation of Photocatalytic Activity and Kinetics of TiO2 Sensitized by Benzidine Yellow G - Du, P.; Shang, X.L.; Li, C.H. (Asian Journal of Chemistry, 2014)
A new TiO2 photocatalyst was sensitized with benzidine yellow G by solvothermal synthesis method and characterized by SEM, XRD and FT-IR. The photocatalytic activity and kinetics of the composite were investigated by the photocatalytic degradation of methylene blue, neutral red and xylenol orange under the visible light irradiation. The results show that the photoresponse of TiO2 has been extended from ultraviolet to visible region. The degradation rate of the three dyes reached to 72-96 %. The kinetics of the photocatalytic degradation process of methylene blue was also been discussed and well conformed to the Langmuir-Hinshelwood kinetics model.